Sosialisasi Pemanfaatan Mikroba Lokal sebagai Sumber Biofertilizer di SMK PP Negeri Mataram - Zulkifli, Lalu; Ayu Citra Rasmi, Dewa; Sakaroni, Rubiyatna; Robi'atul Adawiyah, Marosa; Cahyadi Wirajagat, Gde; Fadilla Yuliana, Baiq (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The intensive use of synthetic chemical fertilizers has led to soil fertility degradation, environmental pollution, and high dependence on expensive production inputs. An environmentally friendly alternative is the use of local microbes as biofertilizers that can dissolve phosphate, fix nitrogen, and produce plant growth hormones. This community service activity aimed to increase the understanding of teachers at SMK PP Negeri Mataram about the role of local microbes in sustainable agriculture, while also providing basic skills in the technique of isolating phosphate-solubilizing bacteria from the rhizosphere. The implementation methods included material socialization, interactive discussions, laboratory practices, and evaluation of understanding through pre-tests and post-tests. The results of the activity showed a significant increase in understanding after the dissemination, with the majority of teachers scoring above 80 on the post-test. Enthusiasm was also evident in the isolation practice, as teachers gained hands-on experience that they had never had before. The impact of this activity not only increased teachers' knowledge of biofertilizers, but also opened up opportunities to integrate local microbe material into the school curriculum as an alternative to environmentally friendly agriculture.